EKSPLOITAS1TUBUH WANITA DALAM FILM HOROR DARAH JANDA KOLONG WEWE NAFSU POCONG - Sunarto, Ucu Andritama; Prilosadoso, Basnendar Herry (Capture : Jurnal Seni Media Rekam, 2013)
This research entitled Darah Janda Kolong Wewe Nafsu Pocong telling the backgroundabout the curiosity about why woman became a main actor or object in the movies in the everyscene. Hence, this research used qualitative concerning how woman image was visualized bysemiotics (Roland Barthes) showed at Darah Janda KolongWewe Nafsu Pocong. In addition, theresult showed that horror movies were commonly visualized with exploitation againts woman'sbody as an vulgar object.Keywords: Woman's body,horror movies,and exploitation